The carboxy-terminal region of mammalian HSP90 is required for its dimerization and function in vivo. - Minami, Y (1994)
The majority of mouse HSP90 exists as alpha-alpha and beta-beta homodimers. Truncation of the 15-kDa carboxy-terminal region of mouse HSP90 by digestion with the Ca(2+)-dependent protease m-calpain caused dissociation of the dimer. When expressed in a reticulocyte lysate, the full-length human HSP90 alpha formed a dimeric form. A plasmid harboring human HSP90 alpha cDNA was constructed so that the carboxy-terminal 49 amino acid residues were removed when translated in vitro. This carboxy-terminally truncated human HSP90 alpha was found to exist as a monomer. In contrast, loss of the 118 amino acid residues from the amino terminus of human HSP90 alpha did not affect its in vitro dimerization. Introduction of an expression plasmid harboring the full-length human HSP90 alpha complements the lethality caused by the double mutations of two HSP90-related genes, hsp82 and hsc82, in a haploid strain of Saccharomyces cerevisiae. The carboxy-terminally truncated human HSP90 alpha neither formed dimers in yeast cells nor rescued the lethal double mutant.